2015
DOI: 10.1111/bph.13118
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide derivative AL‐1 improves insulin resistance through down‐regulation of NFκB signalling pathway

Abstract: BACKGROUND AND PURPOSEAndrographolide is the most active constituent of the medicinal plant Andrographis paniculata. Previously, we synthesized a novel andrographolide derivative AL-1, conjugating andrographolide with lipoic acid. Although the antioxidative and/or anti-inflammatory activity of AL-1 contributes to its cytoprotective effects, whether AL-1 can improve insulin resistance and the mechanisms responsible for its action have not been elucidated. EXPERIMENTAL APPROACHWe investigated the anti-hyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…13 Thus, ALA is able to protect mitochondria from oxidative damage, improves mitochondrial biogenesis and function. [18][19][20] ALA and AL-1 are assumed to be beneficial in IBD, diabetes, brain or cardiovascular dysfunction, cancer, and so on. 16,17 Andrographolid-lipoic acid-1 (AL-1) is a known derivative of ALA, containing andrographolide acid in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…13 Thus, ALA is able to protect mitochondria from oxidative damage, improves mitochondrial biogenesis and function. [18][19][20] ALA and AL-1 are assumed to be beneficial in IBD, diabetes, brain or cardiovascular dysfunction, cancer, and so on. 16,17 Andrographolid-lipoic acid-1 (AL-1) is a known derivative of ALA, containing andrographolide acid in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the development of cholestasis can also result in inflammation and further deterioration. Previous studies have demonstrated that DA can reduce inflammatory responses [38]. To clarify the mechanisms underlying the effect of DA on inflammatory response in the BDL mice with LPS, we assessed the levels of TNF-α and IL-6 expression and NF-κB activation by ELISA and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor plays an important role in cell signal transduction and gene expression regulation, and is also the critical nuclear factor involved in the initiation and regulation of inflammation. In recent years, the inflammatory response mediated by NF-κB is one focus of research into the mechanisms underlying insulin resistance (30,31). Following NF-κB activation, the transcription of inflammatory factors, such as TNF-α, interleukin (IL)-1β and IL-6, is initiated and regulated.…”
Section: Discussionmentioning
confidence: 99%